Disruption of Medical Education in Times of Pandemic: Reflections from the Ground (International Journal of Multidisciplinary Perspectives in Higher Education, 2022)
The COVID-19 pandemic has caused massive disruptions to conventional teaching and learning activities in medical schools worldwide. In this short essay, we discuss our experiences with various sudden changes and obstacles facing academic activities at the Universiti Teknologi MARA (UiTM) Faculty of Medicine in Selangor, Malaysia. We elaborate on the predicaments faced by students, lecturers and university administration during an undergraduate Public Health rotation in which students have to organize health promotion programs and conduct research. Subsequently, we argue that this global health crisis – and its unique impact on students’ academic exercises – calls for an urgent change to student evaluation methods and approach. Taking into account the different restrictions imposed on students and lecturers alike, the old criteria for assessing students’ performance should be reviewed, in order to do justice and ensure objectivity.